Synthesis and characterization of zirconia nanocrystalline powder by thermal treatment method. (2022) - Soni, Dimple; Singh, Jaiveer; Kaurav, Netram; Tripathi, Jitendra; Sharma, Anupam
Abstract: The production of nano crystalline zirconium dioxide using the heat treatment method is described in this present study. Ethylene glycol was used as a surfactant substance to control the size of the nanoparticles. X-ray diffraction (XRD), UV–Vis absorbance spectroscopy, and FT-IR spectroscopy were used to understand the effect of the surfactant material on structural and optical properties. Analysis of XRD provided the average crystallite size of about 4.61 nm for ZrO2 sample, and UV–Vis spectroscopy was used to obtain the band gap energy and it is 5.33 eV. At different wavelengths, the FT-IR spectra revealed various stretching bonds in the ZrO2 compound.